Kepatuhan Pajak: Sebuah Analisis Teoritis Berdasarkan Perspektif Teori Atribusi - Fitri Romadhon; Erlina Diamastuti (Politeknik Negeri Lampung, 2020)
The low level of Indonesia tax ratio, tax revenue realizations, and tax compliance are facts that continue to occur in spite of several efforts made by government to conquer these problems. This imparity comes up with the notion to explore determinants of tax compliance, because by identifying factors that can influence tax compliance, spesific solutions related to those factors can be proposed. This research was conducted by qualitative approach using literature review, through the perspective of attribution theory. By reviewing various articles related to the research topic, it can be inferred that antecedents of tax compliance can be categorized into three factors (internal, external and relational). The implication of this paper for the government is to improve voluntary tax compliance through education, socialization, service quality, institutional governance while maintaining programs to enforce tax payer compliance